Co-administering Melatonin With an Estradiol-Progesterone Menopausal Hormone Therapy Represses Mammary Cancer Development in a Mouse Model of HER2-Positive Breast Cancer - Dodda, Balasunder R.; Bondi, Corry D.; Hasan, Mahmud; Clafshenkel, William P.; Gallagher, Katie M.; Kotlarczyk, Mary P.; Sethi, Shalini; Buszko, Ethan; Latimer, Jean J.; Cline, J. Mark; Witt-Enderby, Paula A.; Davis, Vicki L. (Frontiers in Oncology, 2019)
Melatonin has numerous anti-cancer properties reported to influence cancer initiation, promotion, and metastasis. With the need for effective hormone therapies (HT) to treat menopausal symptoms without increasing breast cancer risk, co-administration of nocturnal melatonin with a natural, low-dose HT was evaluated in mice that develop primary and metastatic mammary cancer. Individually, melatonin (MEL) and estradiol-progesterone therapy (EPT) did not significantly affect mammary cancer development through age 14 months, but, when combined, the melatonin-estradiol-progesterone therapy (MEPT) significantly repressed tumor formation. This repression was due to effects on tumor incidence, but not latency. These results demonstrate that melatonin and the HT cooperate to decrease the mammary cancer risk. Melatonin and EPT also cooperate to alter the balance of the progesterone receptor (PR) isoforms by significantly increasing PRA protein expression only in MEPT mammary glands. Melatonin significantly suppressed amphiregulin transcripts in MEL and MEPT mammary glands, suggesting that amphiregulin together with the higher PRA:PRB balance and other factors may contribute to reducing cancer development in MEPT mice. Melatonin supplementation influenced mammary morphology by increasing tertiary branching in the mouse mammary glands and differentiation in human mammary epithelial cell cultures. Uterine weight in the luteal phase was elevated after long-term exposure to EPT, but not to MEPT, indicating that melatonin supplementation may reduce estrogen-induced uterine stimulation. Melatonin supplementation significantly decreased the incidence of grossly-detected lung metastases in MEL mice, suggesting that melatonin delays the formation of metastatic lesions and/or decreases aggressiveness in this model of HER2+ breast cancer. Mammary tumor development was similar in EPT and MEPT mice until age 8.6 months, but after 8.6 months, only MEPT continued to suppress cancer development. These data suggest that melatonin supplementation has a negligible effect in young MEPT mice, but is required in older mice to inhibit tumor formation. Since melatonin binding was significantly decreased in older mammary glands, irrespective of treatment, melatonin supplementation may overcome reduced melatonin responsiveness in the aged MEPT mice. Since melatonin levels are known to decline near menopause, nocturnal melatonin supplementation may also be needed in aging women to cooperate with HT to decrease breast cancer risk.